Pengaruh Bimbingan Karir terhadap Kesiapan Kerja Siswa SMK Negeri 4 Banda Aceh - Ria Huwaida; Muslima Muslima (EduInovasi: Journal of Basic Educational Studies, 2026)
Work readiness is one the important indicators of the success of vocational education, particularly Vocational High Schools (SMK), in preparing graduates to enter the workforce. This study aims to analyze the effect of career guidance on the work readiness of students at SMK Negeri 4 Banda Aceh. This research employed a quantitative approach of all 66 twelfth-grade students, and the sampling technique used was total sampling. The instruments used were career guidance and work readiness questionnaires based on a Likert scala. Data analysis was conducted using reliability, normality, linearity, and simple regression tests. The Cronbach’s Alpha value for the career guidance variable was 0,896 and for work readiness was 0.889, indicating high realibility. The normality test showed a significance value of 0.076 (>0.05), while the linearity test showed a deviation from linearity significance value of 0.320 (>0.05). These results indicate that the better the implementation of career guidance, the higher the students’ work readiness. This study confirms the importance of systematic career guidance services in improving the work readiness of vocational high school students.